The Results of the Learning Activity Using the Game “Time to Climb” to Improve English Learning Achievement in NEWS Unit for Fifth-Grade High School Students (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
The purposes of this study were to: (1) compare the English learning achievement of Grade 11 students in the News unit before and after using the “Time to Climb” game, and (2) examine students’ satisfaction with learning English in the News unit through the Time to Climb game. The sample consisted of 37 Grade 11/1 students from Donka Wittaya School, selected through cluster sampling. The research instruments included (1) two lesson plans incorporating the game, with an average suitability rating of 4.00, indicating a high level of appropriateness; (2) a 20-item achievement test with item difficulty indices ranging from 0.43 to 0.70, discrimination indices from 0.33 to 0.72, and a reliability coefficient of 0.89; and (3) a 10-item satisfaction questionnaire with a reliability coefficient of 0.92. Data were analyzed using the mean, standard deviation, and a paired-sample t-test. The results revealed that (1) students’ English learning achievement in the News unit significantly improved after using the Time to Climb game at the .05 significance level, and (2) students’ overall satisfaction with learning English in the News unit through the Time to Climb game was high (Mean = 4.29, S.D. = 0.54).